The interpenetration of criminal and lawful economic activities - Wallwaey, Elisa; Havas, Attila; Cuhls, Kerstin (KRTK-KTI working papers, 2022)
As the world economy operates more and more through computerised transactions, new possibilities for intertwining criminal and lawful economic activities open up, as well as new opportunities for law enforcement agencies to fight crime. Considering the tremendous and potentially devastating damages caused by criminal economic activities, the issue should be high on the agenda of policy-makers, including R&I policy-makers. The race between criminal actors and the state trying to protect companies and citizens will be a permanent one. The paper provides and overview of trends and drivers in these domains, highlighting potential disruptions. It also presents four scenarios with a time horizon of 2040 to explore the role of R&I activities and regulations in shaping the possibilities for the interpenetration of criminal and lawful economic activities and derive policy implications. The complex nature of criminal economic activities, their detection, investigation, and prosecution are related to research and innovation in at least three areas. First, research in, and the development and improvement of, information and communication technologies necessary to monitor, track and analyse criminal activities. Second, regulatory techniques for preventing innovators from i) moving outside the sphere of lawful activities; ii) moving too far and entering a grey zone where regulation is missing; and iii) settling on clear-cut criminal behaviour. Third, research in, and the development and improvement of, forensic techniques of reconstructing what actually happened, and thus attributing responsibility for crime.
Keywords: Graue Literatur